Faktor-Faktor yang Berhubungan dengan Kejadian ISPA pada Balita - Dita Lazamidarmi; Rico Januar Sitorus; Heru Listiono (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
ISPA is an infectious disease of the upper and lower respiratory tract which is caused by the entry of microorganisms (bacteria and viruses) into the respiratory tract organs which lasts for 14 days. This study aims to determine the relationship between ventilation, type of house floor, type of fuel. for cooking, completeness of immunization and history of infectious disease against the incidence of ARI in children under five. This type of research is quantitative, using the analytical survey method with a cross-sectional approach. The research location is in the working area of the Alang-Alang Lebar Community Health Center in Palembang City with a total of 78 respondents. The primary data source was obtained by means of a questionnaire and secondary data was obtained from the profile and records of the Alang-Alang Lebar Community Health Center Palembang. Data analysis consisted of univariate and bivariate analysis using the chi square test. The results of the chi square test showed that the variables associated with the incidence of ARI in children under five were ventilation (p = 0.000 ≤ 0.05), and a history of infectious diseases (p = 0.039 ≤ 0.05). Based on the results of the study and discussion, it was concluded that there was a simultaneous relationship between ventilation and a history of infectious diseases simultaneously with the incidence of ARI in children under five in the Alang-alang Lebar Community Health Center Palembang City in 2020.